Preschoolers Use Emotion in Speech to Learn New Words. Issue 5 (25th February 2013) - Berman, Jared M. J.; Graham, Susan A.; Callaway, Dallas; Chambers, Craig G.
Abstract : Two experiments examined 4‐ and 5‐year‐olds' use of vocal affect to learn new words. In Experiment 1 ( n = 48), children were presented with two unfamiliar objects, first in their original state and then in an altered state (broken or enhanced). An instruction produced with negative, neutral, or positive affect, directed children to find the referent of a novel word. During the novel noun, eye gaze measures indicated that both 4‐ and 5‐year‐olds were more likely to consider an object congruent with vocal affect cues. In Experiment 2, 5‐year‐olds ( n = 15) were asked to extend and generalize their initial mapping to new exemplars. Here, 5‐year‐olds generalized these newly mapped labels but only when presented with negative vocal affect.